Does government policy matter in the digital transformation of farmers’ cooperatives?—A tripartite evolutionary game analysis - Zheng, Yangyang; Mei, Linfeng; Chen, Weimin (Frontiers in Sustainable Food Systems, 2024)
Farmers' cooperatives, as one of the new types of agricultural businesses, are an effective carrier for the digital transformation of agriculture, yet existing studies have paid less attention to how farmers' cooperatives realize digital transformation. As agricultural economic organizations embedded in social networks, the digital transformation of farmers' cooperatives requires the joint efforts of governments and companies. Based on the evolutionary game theory, this paper constructs a tripartite evolutionary game model of the government, digital technology companies and farmers' cooperatives, and simulates and analyzes the behavioral decisions of different participants in the digital transformation of farmers' cooperatives from the perspective of government policy. The results show: Medium government subsidies can effectively promote the digital transformation of farmers' cooperatives, and strong subsidy policies increase the government's financial burden, which is not conducive to policy sustainability. Strong government regulation facilitates digital technology companies to actively provide high-quality services for the digital transformation of farmers' cooperatives, but government regulation does not have a significant impact on the strategic choices of the government and farmers' cooperatives. When farmer cooperatives and digital technology companies are in a medium or high level of cooperative trust or when the number of labors saved by digital transformation reaches a certain level, farmers'farmer cooperatives opt for digital transformation even if the government withdraws from policy intervention.